TIC’s, as a tools against insecurity in cities (Research, Society and Development, 2021)
This article seeks to analyze the use of information and communication technologies (TIC’s) as a differentiating element that supports public safety activities, helping to reduce insecurity and favoring the development of safer cities. Recognizing insecurity as a growing problem and considering that there is not a detailed analysis of technological tools used to prevent it, the findings found in two cities in the Bogotá and Mexico City regions are shown. In the process to obtain the information, documentary investigation techniques were used in retrospect on TIC’s, main crimes and applicable regulations. From the analysis carried out, similar operating processes and advances using these tools, but not at the pace demanded by this challenge were found. As well as the need to review the regulatory part for cybersecurity, cyberspace and protocols to face a possible cyber-attack. From the results obtained, it is shown that insecurity is a priority challenge to continue facing, that technology is here to stay and that it is necessary to advance in an integrated way not only in cities but at the regional level to achieve a real difference and the development level required in the future to form sustainable smart cities.